Best surgical option for arch extension of type B dissection: the endovascular approach - Kuratani, Toru (Annals of Cardiothoracic Surgery; Vol 3, No 3 (May 31, 2014): Type B Aortic Dissection (I), 2014)
Despite advances in surgical techniques and postoperative management, the in-hospital mortality rate for patients undergoing conventional open surgical repair for type B dissections is still significant. In light of this, the less invasive surgical procedure for acute type B aortic dissections, defined as thoracic endovascular aortic repair (TEVAR), was developed. Despite some controversy, the use of TEVAR for the management of type B aortic dissections has become commonplace. Generally, the main entry tear in type B aortic dissection is located in the vicinity of the orifice of the left subclavian artery (LSA). The proximal landing zone in the aortic arch must be secured as long as the aim of TEVAR for type B dissection is primary entry closure. This requires hybrid surgery that includes the use of open surgical procedures, such as debranching for revascularization of cervical branches. Despite the presence of challenging anatomic conditions in the aortic arch, hybrid repair has evolved as an increasingly viable alternative, and promising early and long-term results have been reported. As the next step, fenestrated and branched TEVAR techniques have recently been reported with satisfactory early results. In the coming years, there will be intense competition to develop the devices themselves, improve delivery systems, and supplement devices with auxiliary functions. Thus there is high expectations for the next generation and how they will improve and advance treatment methods of TEVAR for type B aortic dissections.